Achieving Goal 16 of the Sustainable Development Goals and Environmental Lessons for Malaysia. Issue 2 (November 2019) - Tan, Sarah
Abstract: On September 2015, countries around the world pledged to end poverty, protect the planet, and hit specific developmental targets within fifteen years at the signing of th|e United Nations 2030 Agenda. Within the 2030 Agenda are seventeen Sustainable Development Goals (SDG). Goal 16 of the SDG contains twelve targets; of these, Target 16.3 is aimed at ensuring equal access to justice for all and Target 16.10 at ensuring public access to information. Malaysia as a signatory has pledged its commitment to fulfilling these SDGs. This paper's primary focus is on the fulfilment of Targets 16.3 and 16.10 within Malaysia's legal environmental framework. At present, there are provisions that ensure equal access to justice and those that ensure public access to information; however, it is suggested that these are insufficient, uncommon, and limited. This paper proposes an amendment to the Federal Constitution to include the express right to a clean environment, and demonstrates, through comparative study, the success similar provisions have had on the environmental protection laws of other countries such as India, the Philippines, South Africa, Nepal, the Netherlands, and Nigeria. It then considers what possible lessons Malaysia could glean from these national experiences in fulfilling its goals for Targets 16.3 and 16.10 before concluding with the proposition that Malaysia should consider an express constitutional right to a clean environment if she intends to meet her SDG goals.